Rectal gastrointestinal stromal tumors: Imaging features with clinical and pathological correlation - Jiang, Zhao-Xia (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate computed tomography (CT) and magnetic resonance imaging (MRI) manifestations of rectal gastrointestinal stromal tumors (GISTs) in order to enhance the recognition of these rare tumors. METHODS: Fourteen patients with pathologically proven rectal GISTs were retrospectively reviewed. Patient histories were retrospectively reviewed for patient age, gender, presenting symptoms, endoscopic investigations, operation notes and pathologic slides. All tumors were evaluated for CD117, CD34 expression, and the tumors were stratified according to current criteria of the National Institutes of Health (NIH). In all cases the first pre-operation imaging findings (CT and MRI, n = 3; MRI only, n = 8; CT only, n = 3) were analyzed by two experienced radiologists by consensus, which include: tumor size, shape, CT density (hypodense, isodense and hyperdense), MRI signal intensity (hypointense, isointense and hyperintense), epicenter (intraluminal or extraluminal), margin (well-defined or ill-defined), internal component (presence of calcifications, necrosis, hemorrhage or ulceration), pattern and degree of enhancement, invasion into adjacent structures. After review of the radiologic studies, clinical and pathological findings were correlated with radiological findings. RESULTS: The patients, 13 men and 1 woman, were aged 31-62 years (mean = 51.5 ± 10.7 years). The most common initial presentation was hematochezia (n = 6). The mean tumor diameter was 5.68 ± 2.64 cm (range 1.5-11.2 cm). Eight lesions were round or oval, and 6 lesions were irregular. Eleven lesions were well-defined and 3 had ill-defined margins. Ten tumors were extraluminal and 4 were intraluminal. The density and MR signal intensity of the solid component of the lesions were similar to that of muscle on unenhanced CT (n = 6) and T1-weighted images (n = 11), and hyperintense on T2-weighted MR images. Calcification was detected in 2 tumors. Following intravenous injection of contrast media, 3 lesions had mild enhancement and 11 lesions had moderate enhancement. Enhancement was homogenous in 3 lesions and heterogeneous in 11. In 1 of 11 patients who underwent both CT and MRI, the tumor was homogenous on CT scan and heterogeneous on MRI. Eight patients were classified as high risk according to the modified recurrent risk classification system of NIH. CONCLUSION: Rectal GISTs usually manifest as large, well-circumscribed, exophytic masses with moderate and heterogeneous enhancement on CT and MRI. The invasion of adjacent organs, bowel obstruction and local adenopathy are uncommon.